2020
DOI: 10.1371/journal.pone.0228209
|View full text |Cite
|
Sign up to set email alerts
|

Sinking of microbial-associated microplastics in natural waters

Abstract: Degraded plastic debris has been found in nearly all waters within and nearby urban developments as well as in the open oceans. Natural removal of suspended microplastics (MPs) by deposition is often limited by their excess buoyancy relative to water, but this can change with the attachment of biological matter. The extent to which the attached biological ballast affects MP dynamics is still not well characterised. Here, we experimentally demonstrate using a novel OMCEC (Optical Measurement of CEll colonisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 61 publications
(96 reference statements)
1
40
0
2
Order By: Relevance
“…In the present study, there was a significant positive relationship between soil temperature (daily average ranging from 17.1 to 20.1 • C during dry season) and MP abundance in the dry (winter) season (Table 3). Soil temperature may influence microbial activity and colonisation on MPs, thereby influencing microbial degradation of MPs and their transport and sinking in natural waters [92]. Importantly, the rate of plastic fragmentation is dependent on temperature [7].…”
Section: Relationship Between Microplastics In Mangrove Sediment and mentioning
confidence: 99%
“…In the present study, there was a significant positive relationship between soil temperature (daily average ranging from 17.1 to 20.1 • C during dry season) and MP abundance in the dry (winter) season (Table 3). Soil temperature may influence microbial activity and colonisation on MPs, thereby influencing microbial degradation of MPs and their transport and sinking in natural waters [92]. Importantly, the rate of plastic fragmentation is dependent on temperature [7].…”
Section: Relationship Between Microplastics In Mangrove Sediment and mentioning
confidence: 99%
“…77,78 However, PMD sinking uxes are largely understudied and the deposition mechanisms by which the microplastics reach the sediments is not yet fully understood. [79][80][81][82][83][84][85][86] It is also unclear if sunken (but previously oating) PMD remains at the seaoor or if sedimented plastics could become aoat again once the coating biolm is (partially) degraded. 4 Indeed, the ndings of an abundance of suspended PMD in the mid water column 79,86 begs the question if plastics may not only oat or sink but might also oscillate in the water column.…”
Section: Missing Plastic In the Oceanmentioning
confidence: 99%
“…The effects of interactions between biogenic material (such as marine snow 310 and marine microalgae 77,91,103,116 ) and very small, sub-millimetre microplastics (down to 2 µm) have in fact been investigated in a number of laboratory studies. These studies, however, have either focussed on heteroaggregation 38,77,91,103,116 , rather than the colonisation of individual microplastic particles or polymers that are denser than seawater 38 (and would therefore readily sink in the marine environment even without biofouling). These studies have found that heteroaggregation can either increase or decrease the settling or rising velocity of microplastics or even change the direction of their movement altogether (i.e., making buoyant polymers sink and non-buoyant polymers float/rise), depending on the polymer type and the composition of the heteroaggregates 38,77,91,103,116 .…”
Section: Effects Of Microbe-plastic Interactions On Plastic Buoyancy and Transportmentioning
confidence: 99%
“…Despite a number of studies having been published on the sinking and rising behaviour of microplastics incorporated into heteroaggregates, the experimental data needed to enable comparisons between empirical data and mathematical model (e.g. 38,151,304,[312][313][314] ) predictions is lacking 151,314,315 , specifically: (i) on the effects of microbial biofouling on the buoyancy of individual sub-millimetre microplastics; and (ii) on natural marine biofilm parameters, namely biofilm thickness and density 151 . Further impacts of microbial colonisation on the vertical transport of plastics are related to the ingestion of plastics by macroorganisms 5,316,317 , although micro-eukaryotes, including marine dinoflagellates 91 and ciliates 318 , have also been observed to ingest small microplastics, possibly making microplastics more bioavailable for marine organisms at higher trophic levels 318 .…”
Section: Effects Of Microbe-plastic Interactions On Plastic Buoyancy and Transportmentioning
confidence: 99%